Developmental Validation of a Rapidly Mutating Y-STR Panel Labeled by Six Fluoresceins for Forensic Research - Jin, Xiaoye; Zhang, Hongling; Ren, Zheng; Wang, Qiyan; Liu, Yubo; Ji, Jingyan; Zhang, Han; Yang, Meiqing; Zhou, Yongsong; Huang, Jiang (Frontiers in Genetics, 2022)
The male-specific region of the human Y chromosome is a useful genetic marker for genealogical searching, male inheritance testing, and male DNA mixture deconvolution in forensic studies. However, the Y chromosomal short tandem repeats (Y-STRs) are difficult to distinguish among related males due to their low/medium mutation rate. In contrast, rapidly mutating (RM) Y-STRs exhibit unusually high mutation rates and possess great potential for differentiating male lineages. In this study, we developed a novel Y-STRs multiplex amplification assay of 32 RM Y-STRs by fragment analysis using six dye-labeled technology (FAM, HEX, TAMRA, ROX, VIG, and SIZ). The development and the validation of the kit were carried out in accordance with the Scientific Working Group guidelines on DNA Analysis Methods. Identical allelic profiles of the 32 RM Y-STRs using a DNA 9948 sample as the positive control could be observed at different concentrations of PCR reagents. Further, the RM Y-STRs did not show cross-reactions with other common animal species and the developed assay could tolerate interferences from common PCR inhibitors and mixed DNA samples. More importantly, the kit showed relatively high sensitivity and could detect trace DNA samples. Genetic distributions of 32 RM Y-STRs in the Guizhou Han population revealed that these RM Y-STRs showed relatively high genetic diversities. In conclusion, the RM Y-STR assay developed here showed good species specificity, high sensitivity, tolerance to inhibitors, and sample compatibility, which can be viewed as a highly efficient tool with high discrimination capacity for forensic male differentiation.